The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1002/elan.201000629
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Application of Mediator‐Free H2O2 Biosensors of Graphene‐Fe3O4 Composites

Abstract: Graphene-Fe 3 O 4 (G-Fe 3 O 4 ) composites were prepared with a solvothermal method for the immobilization of horseradish peroxidase (HRP) to construct a mediator-free H 2 O 2 biosensor. The morphology and structure of the GFe 3 O 4 composites were analyzed by TEM, SEM, and XRD. Chitosan (CH) was utilized to disperse the composites, and the mixture of CH, G-Fe 3 O 4 and HRP was spin-coated on an indium tin oxide (ITO) electrode to form a biocomposites film. Electrochemical impedance spectroscopy (EIS) and cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(30 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Graphene–metal oxide nanoparticle composites (e.g., ZnO, 57 TiO 2 , 58 Fe 3 O 4 , 59 SnO 2 , 60 ) are, by far, the most common hybrids synthesized using the hydrothermal method. Specifically, metal oxide nanoparticles can provide the graphene–metal oxide nanoparticle hybrids with a number of advantages such as a higher capacitance, which depends on the nanoparticle structure, size, and crystallinity, while suppressing agglomeration and the restacking of graphene.…”
Section: Synthesis and Characterization Of Graphene–nanoparticle Hmentioning
confidence: 99%
“…Graphene–metal oxide nanoparticle composites (e.g., ZnO, 57 TiO 2 , 58 Fe 3 O 4 , 59 SnO 2 , 60 ) are, by far, the most common hybrids synthesized using the hydrothermal method. Specifically, metal oxide nanoparticles can provide the graphene–metal oxide nanoparticle hybrids with a number of advantages such as a higher capacitance, which depends on the nanoparticle structure, size, and crystallinity, while suppressing agglomeration and the restacking of graphene.…”
Section: Synthesis and Characterization Of Graphene–nanoparticle Hmentioning
confidence: 99%
“…H 2 O 2 is one of the reactive oxygen species (ROS) amongst others like superoxide anion (O 2 •− ), hydroxyl radical (OH • ), hydroxyl ion (OH − ). The higher concentration of H 2 O 2 is associated with diabetes, atherosclerosis, and ageing, as it generates free hydroxyl radicals, which cause oxidative damage to the tissue components such as lipids and proteins beside DNA [2,3]. For the measurement of H 2 O 2 in biological fluids, several sensitive methods based on horseradish peroxidase (HRP) and artificial substrates (such as Amplex Red and 3,5,3′,5′-tetramethylbenzidine) or on ferrous oxidation in the presence of xylenol orange (FOX) have been developed [4].…”
Section: Introductionmentioning
confidence: 99%
“…To these goals, several graphene‐based electrochemical sensors have been developed for sensitive H 2 O 2 detection 42. Dong’s group first reported that chemically reduced graphene oxide (GO) possessed superior electrocatalytic activity toward H 2 O 2 43, 44. Liu et al.…”
Section: 2d‐layered Nanomaterials‐based Electrochemical Sensorsmentioning
confidence: 99%